Separation and characterization of glucosylated protein in human serum - Kanamaru, Ikue; Konno, Kunio; Nishimura, Toshiro; Makino, Yoshiaki (SEIBUTSU BUTSURI KAGAKU, 1987)
The nonenzymatic glucosylation reaction occurs in various proteins of the body, particularly in diabetic subjects. Glucosylated human albumin was prepared by incubating albumin with glucose in the presence or absence of sodium cyanoborohydride (NaCNBH3) for 2 weeks at 37°C. We prepared a newly boronate affinity chromatography system by connecting 3-aminophenyl boronic acid hemisulfate with CNBr-activated Sepharose 4B. Using this system, synthetic glucosylated albumin, normal serumm and diabetic were applied to this Boronate Sepharose column. Pure glucosylated protein was separated from them. Glucosylated albumin levels to the total albumin were 49% in the synthetic nonreduced glucosylated albumin. Glucosylated protein levels to the total protein were determined in 5 of the diabetic subjects and ranged from 10.4% to 15.7% (mean±SD 11.2±2.0). Glucosylated protein levels ranged from 5.6 to 8.0 (mean±SD 6.9±0.9) in 5 of the normal subjects. Glucosylated protein values were significantly greater in diabetic subjects than in normal subjects. The reduced glucosylated albumin moved more rapidly than nonglucosylated albumin and nonreduced glucosylated albumin on agarose electrophoresis. However, the reduced glucosylated albumin on polyacrylamide electrophoresis moved a little more rapidly than the other albumins. A male rabbit was immunized with human reduced glucosylated albumin. On day 120 blood was obtained for our studies. To document the presence of antibodies, we used the Ouchterlony method and confirmed an antibody against reduced glucosylated albumin.